Controlling interpenetration through linker conformation in the modulated synthesis of Sc metal–organic frameworks. Issue 3 (2nd January 2018) - Marshall, Ross J.; Lennon, Ciaran T.; Tao, Andi; Senn, Hans M.; Wilson, Claire; Fairen-Jimenez, David; Forgan, Ross S.
Abstract : Linker conformation controls interpenetration in two structurally analogous scandium metal–organic frameworks, one of which can be defect engineered by coordination modulation to introduce hierarchical porosity. Abstract : Interpenetration in metal–organic frameworks (MOFs), where multiple nets of metal ions or clusters linked by organic ligands are nested within each other's pore spaces, affects important physical properties such as stability and gas uptake, and can be controlled through ligand sterics and modifying synthetic conditions. Herein, we extend the use of coordination modulation – deliberate addition of competing monotopic ligands to syntheses – to prepare Sc MOFs containing related biphenyl-4, 4′-dicarboxylate (bpdc) and 2, 2′-bipyridine-5, 5′-dicarboxylate (bpydc) linkers. The Sc-bpdc MOF adopts a two-fold interpenetrated structure, however, the Sc-bpydc MOF is non-interpenetrated, despite only minor electronic modifications to the ligand. A comprehensive experimental and theoretical examination reveals that ligand twisting (energetically favourable for bpdc but not bpydc) and associated π-stacking interactions are a prerequisite for interpenetration. The more rigid Sc-bpdc is susceptible to modulation, resulting in differences in morphology, thermal stability and the synthesis of a highly defective, acetate-capped mesoporous material, while the large pore volume of Sc-bpydc allows postsynthetic metallation with CuCl2 in a single-crystal to single-crystal manner. Controlling interpenetration through linker conformation could result in design of new materials with desirable properties such as bifunctional solid-state catalysts.